2016
DOI: 10.1016/j.neulet.2016.03.036
|View full text |Cite
|
Sign up to set email alerts
|

Central effect of vasotocin 4 receptor (VT4R/V1aR) antagonists on the stress response and food intake in chicks given neuropeptide Y (NPY)

Abstract: Previous studies identified SR-49059 as a most effective antagonist of the avian vasotocin 4 receptor (VT4R) compared to other candidate blockers including the Manning compound using in silico 3 dimensional (3D) modeling/docking analysis of the chicken VT4R and an in vitro anterior pituitary cell culture study. The present experiments were designed to validate whether SR-49059 and the Manning compound would likewise be effective in vivo in blocking the VT4R when applied intracerebroventricularly (ICV) to chick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Similar results were obtained from the studies of avian AVT V1a receptor, which is highly homologous to mammalian AVP V1a receptor, and is associated with the regulation of food intake in chickens by modulating neurons that synthesize and release anorexigenic neuropeptides [ 68 , 69 ].…”
Section: Avp and Food Intakesupporting
confidence: 79%
“…Similar results were obtained from the studies of avian AVT V1a receptor, which is highly homologous to mammalian AVP V1a receptor, and is associated with the regulation of food intake in chickens by modulating neurons that synthesize and release anorexigenic neuropeptides [ 68 , 69 ].…”
Section: Avp and Food Intakesupporting
confidence: 79%
“…26,27 NPY in the ROT has been suggested to be involved with vasotocin (VT) in controlling feeding response in birds. 49,50 However, our results showed that the nucleus that responded to food restriction is the PVN. Therefore, future research is required to confirm whether NPY in the area around the ROT contributes with VT in regulation of food intake in birds.…”
Section: Discussionmentioning
confidence: 51%
“…In goldfish, intracerebroventricular injections of AVT have an anorexigenic effect, with fish decreasing their cumulative food intake in a dose‐dependent response (Araishi, Watanabe, Yamazaki, Nakamachi, & Matsuda, 2019). Similarly, central mesotocin administration in chicks, but not peripheral administration, inhibits feeding behaviors (Masunari, Cline, Khan, & Tachibana, 2016), and AVT modulates NPY‐induced food intake (Kuenzel, Hancock, Nagarajan, Aman, & Kang, 2016). Perhaps this population of avt cells in A .…”
Section: Discussionmentioning
confidence: 99%